Flux-lattice melting, anisotropy, and the role of interlayer coupling in Bi-Sr-Ca-Cu-O single crystals - Duran, C. (1991)
Fil: Duran, C. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina